A case of pulmonary aspergillosis in white storks - GULCUBUK, A.; ERDOGAN-BAMAC, O.; METINER, K.; YUZBASIOGLU OZTURK, G.; OZGUR, Y.; HAKTANIR, D. (Journal of the Hellenic Veterinary Medical Society, 2018)
Aspergillosis is a fungal infection affecting respiratory system both in mammals and avian species. It is more commonly encountered in birds, in comparison with its mammalian counterpart. Mostly isolated strains are Aspergillus fumigatus (95%) and Aspergillus flavus (5%). Affected lungs and air sacs reveal miliary to gross lesions like gray-yellowish or white-grayish granulomatous foci surrounded by white halos indicative of inflammatory infiltration. Five storks found dead in the rural areas near Istanbul were submitted to our faculty between years 2008 and 2014. Two of them were thought to be younger than 1-year-old and the other three were older than one year of age. Necropsies were performed right after their submissions. Aspergillosis lesions were observed in the lungs and thoracic air sacs of the first four storks. In addition to these changes the lesions were detected at the aortic bifurcation and on the testicular and renal capsule of the fifth stork. Histopathology revealed encapsulated granulomas with foci of caseous necrosis at the center surrounded by numerous macrophages, heterophil leukocytes, lymphocytes and foreign body giant cells in all the storks. Following the gross, histopathological and mycological examinations the agents were detected as Aspergillus fumigatus. Although, the number of reported deaths due to Aspergillosis is not high in storks, we believe that these birds are quite susceptible to the disease and stress factors such as migration increases the risk of pathogenicity. This report was designed as a contribution to literature since there is only one reported case available with respect to aspergillosis associated death in storks and stress factors such as migration may also predispose storks to the disease.